The Impact of Indonesia’s Banks Performance towards Banks’ Stock Price (Listed in Indonesia Stock Exchange from 2011 – 2013) Using CAMEL Analysis - Albertus Andre Sujarwo (iBuss Management, 2015)
Although banking industry in Indonesia is facing dynamic challenges every year, banking industry in Indonesia is considered as one of most profitable sectors in Indonesia. This occurance leads to investor preferance in banking industry stocks. In this research, it is believed, profitability is not the only measurement of bank performance which affect stock price. In this problem, other factors as formulated through CAMEL analysis (Capital Adequacy, Asset Quality, Management Quality, Earnings, Liquidity) is a bank performance measurement which affect bank stock price. This research has successfully collected data of 31 banks in Indonesia listed at Indonesia Stock Exchange from 2011 – 2013. Those data is processed with linear regression analysis which proves that CAMEL analysis has significant impact towards bank stock price simultaneously. Partially, only Asset Quality, Management Quality, and Earnings have significant impact towards bank stock price. Keywords: Bank Performance, Stock Price, and CAMEL Analysis.